The Influence of Service Quality, Product Quality, and Price Perception on Purchase Intention through Consumer Satisfaction as an Intervening Variable (Case Study at the Sinar Mas Karanganyar Electronic Store) - Susanti, Nani Irma; Widitya, Asna Ayu; Suyoko, Yohanes; Sumaryanto, Sumaryanto (Sekolah Tinggi Ilmu Ekonomi Semarang, 2024)
The purpose of this problem study is to determine the real impact related to customer satisfaction that is not optimal and buying interest in Sinar Mas Karanganyar Electronic Store related to service quality, product quality and Price Perception. The population of this study was customers as many as 100 respondents.Data collection method with questionnaire method The analytical test tool used is SmartPLS v.3.2.7 with SEM Analysis (Structural Equation Modeling). The results of this study show that Product Quality, Service Quality and Price Perception affect Consumer Satisfaction. While Product Quality, Service Quality, Price Perception and Consumer Satisfaction do not affect Consumer Buying Interest.